What is the Effect of Learning from Home Policy on the Perspectives of Islamic Boarding School Graduates (Pesantren) on Digital Learning in Higher Education ? - Nuril Mufidah; Lubna Farah Khan (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2020)
This article aims to describe the impact of government policies on learning from home and the effects on student perspectives on learning Online learning. The method used is descriptive qualitative with observation instruments, online surveys, discussion group forums with the research subjects of students majoring in Arabic language education graduates of Islamic boarding schools in 2019 at UIN Maulana Malik Ibrahim Malang, Indonesia. Research results are utilized on campus e-learning, which is integrated with SIAKAD and other applications such as WhatsApp and Zoom as well as Google Meet for teleconference facilities during student presentations and discussions. Islamic boarding school graduate students can take online lectures well. The student's perspective on online lectures after the learning from home policy is not suitable due to internet connection constraints and lectures using the assignment method only. Keywords: Learning from Home; online; digital learning; students perspective, higher education Abstrak Artikel ini bertujuan untuk mendeskripsikan dampak kebijakan pemerintah pada pembelajaran dari rumah dan pengaruhnya terhadap perspektif mahasiswa dalam pembelajaran Online. Metode yang digunakan adalah deskriptif kualitatif dengan instrumen observasi, survei online, forum diskusi kelompok dengan subjek penelitian mahasiswa jurusan bahasa Arab lulusan pesantren tahun 2019 di UIN Maulana Malik Ibrahim Malang, Indonesia. Hasil penelitian menunjukkan kampus memanfaatkan e-learning kampus yang terintegrasi dengan SIAKAD dan aplikasi lain seperti WhatsApp dan Zoom serta fasilitas Google Meet untuk telekonferensi untuk presentasi dan diskusi. Mahasiswa alumni pondok pesantren bisa mengikuti perkuliahan online dengan baik. Perspektif mahasiswa terhadap perkuliahan online setelah kebijakan belajar dari rumah kurang baik. Hal ini karena kendala koneksi internet dan perkuliahan hanya menggunakan metode tugas. Kata Kunci: Belajar dari rumah; online; pembelajaran digital; perspektif mahasiswa, pendidikan tinggi